2021
DOI: 10.1021/acsomega.1c03673
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Calculation of the Effects of H2O on Oxygen Functional Groups during Coal Spontaneous Combustion

Abstract: The effects of H2O on the low-temperature oxidation characteristics of coal have always been one of the keys in the research of coal spontaneous combustion, but most studies rely on experiments for macroscopic derivation, and theoretical researches at the microlevel are rarely mentioned. In this paper, phenylacetaldehyde, phenylethyl alcohol, phenylacetic acid, and ethylbenzene hydroperoxide were used as modeling compounds of coal molecules containing aldehyde (−CHO), alcohol hydroxyl (−OH), carboxyl (−COOH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…From previously published studies, the ESP of the red region of the molecular structure is positive, and the darker the color is, the more likely it is that the nucleophilic reactions occur; while the ESP in the blue region is negative, and the darker the color is, the more likely it is that the electrophilic reactions occur . Statistically, the reactive site and its ESP value of each molecule are shown in Table , and it can be seen that the ESP near the H37 atom of the GSH molecule is extremely large, which can readily provide electrons to react with the reactive groups and is a nucleophilic reagent.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…From previously published studies, the ESP of the red region of the molecular structure is positive, and the darker the color is, the more likely it is that the nucleophilic reactions occur; while the ESP in the blue region is negative, and the darker the color is, the more likely it is that the electrophilic reactions occur . Statistically, the reactive site and its ESP value of each molecule are shown in Table , and it can be seen that the ESP near the H37 atom of the GSH molecule is extremely large, which can readily provide electrons to react with the reactive groups and is a nucleophilic reagent.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, the selection of inhibitors is poorly targeted, the identification of determinant reactive groups is missing, and there is a significant lack of research correlating the inhibiting effects with the chemical structures change in the coal. Wang, Qi, and Zhu et al established and refined the chain reaction model of COLT, and the results demonstrated that alkyl radicals, alkoxy radicals, hydroxyl radicals, and peroxyl radicals are the main reactive substances. Accordingly, the search for an inhibitor that could inert them is a top priority of current research.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the adsorption strength of different oxygen-containing functional groups (OFGs) for H 2 O molecules using the DFT, and based on the analysis of the electron density and potential energy density, the order of the capacity of four different OFGs to adsorb H 2 O molecules was found to be Ph–C–O–OH > Ph–COOH > Ph–OH > Ph–CHO. 24 Wang et al studied the interaction between H 2 O molecules and OFGs using the quantum chemical DFT and concluded that the order of influence of the H 2 O molecules on the adsorption stability of the OFGs was carboxyl group > phenolic hydroxyl group > aldehyde group > ether and that the OFGs could improve the wettability on the surface of coal molecules. 25 Xiang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The low-grade coal is about 190 billion tons, accounting for 41.18% of the total coal reserves. 3 6 Coal spontaneous combustion is a common disaster phenomenon in the process of coal mining, storage, and utilization. Coal spontaneous combustion will produce toxic and harmful gases such as CO, CO 2 , SO 2 , and NO.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the coal is still the main production energy and raw material in the world, accounting for 30% of the world’s energy consumption, while Asia’s coal consumption accounts for about 75% of the world. , China is rich in coal resources, accounting for more than 67.5% of disposable energy, but the quality is poor. The low-grade coal is about 190 billion tons, accounting for 41.18% of the total coal reserves. Coal spontaneous combustion is a common disaster phenomenon in the process of coal mining, storage, and utilization. Coal spontaneous combustion will produce toxic and harmful gases such as CO, CO 2 , SO 2 , and NO.…”
Section: Introductionmentioning
confidence: 99%